2020
DOI: 10.5114/pg.2019.85248
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between reflux symptoms and glycogenic acanthosis lesions of the oesophagus

Abstract: Introduction: Glycogenic acanthosis (GA) is a benign, polypoid lesion frequently seen in upper endoscopy with little known aetiology. Information about how it occurs and its clinical significance is lacking. Aim: In this study, the relationship between GA and reflux symptoms was investigated in patients who underwent endoscopy due to reflux symptoms. Material and methods: Sixty patients undergoing endoscopy for reflux symptoms and 60 controls without reflux symptoms were included in the study. Among the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
2
0
4
Order By: Relevance
“…A acantose glicogênica é uma lesão polipóide, benigna, que geralmente é encontrada por meio da endoscopia digestiva alta, porém, a sua relevância clínica ainda não foi estabelecida. Histologicamente, a AG é caracterizada por placas multifocais com conteúdo de epitélio escamoso hiperplásico e de depósitos intracelulares de glicogênio (Yılmaz, 2020). A associação entre AG e esofagite ainda é controversa (Stern, et al, 1980).…”
Section: Discussionunclassified
“…A acantose glicogênica é uma lesão polipóide, benigna, que geralmente é encontrada por meio da endoscopia digestiva alta, porém, a sua relevância clínica ainda não foi estabelecida. Histologicamente, a AG é caracterizada por placas multifocais com conteúdo de epitélio escamoso hiperplásico e de depósitos intracelulares de glicogênio (Yılmaz, 2020). A associação entre AG e esofagite ainda é controversa (Stern, et al, 1980).…”
Section: Discussionunclassified
“…Glycogenic acanthosis is a common benign lesion reported as an incidental finding in 3.5% of esophageal endoscopies (1,2). Macroscopically described as patches of round, elevated, iodine‐positive lesions involving normal esophageal mucosa (3), its incidence increases with age (1).…”
Section: Figurementioning
confidence: 99%
“…A literature search described it in children with celiac disease (4) but no specific reports on its association with pediatric EoE were found. Although historically it has been strongly associated with gastroesophageal reflux disease (1,3), a recent study suggested this may be due to increased incidence of gastroesophageal reflux disease with age (2).…”
Section: Figurementioning
confidence: 99%
“…Vì vậy, nó được phát hiện tình cờ qua nội soi do bệnh nhân đi khám với các triệu chứng của trào ngược dạ dày thực quản (GERD) hoặc viêm loét dạ dày -hành tá tràng. Glycogenic acanthosis được cho là có liên quan đến GERD và thoát vị hoành trượt (hiatal hernia) [1], [2], [4], [5].…”
Section: đặT Vấn đềunclassified
“…Trước đây, TSTBVTQ được cho là lành tính, vì vậy cho nên có rất ít nghiên cứu về bệnh này. Theo một số nghiên cứu, tỷ lệ mắc bệnh khoảng 28,3% và có sự đồng thuận cho rằng TSTBVTQ liên quan tỷ lệ thuận với GERD và thoát vị hoành trượt [3], [5]. Thực tế lâm sàng cho thấy, có một tỷ lệ TSTBVTQ kèm dị sản ruột và một số trường hợp có loạn sản tế bào biểu mô vảy ở các mức độ khác nhau.…”
Section: Bàn Luậnunclassified